Isolation and Structural Identification of New Diol Esters of Okadaic Acid and Dinophysistoxin-1 from the Cultured Prorocentrum lima - Yeong Kwang Ji; Semin Moon; Sangbum Lee; Yun Na Kim; Eun Ju Jeong; Jung-Rae Rho (Toxins)
Prorocentrum, a dinoflagellate responsible for producing diarrhetic shellfish poisoning (DSP) toxins, poses significant threats to marine ecosystems, aquaculture industries, and human health. DSP toxins, including okadaic acid (OA), dinophysis toxin (DTX), and their diverse derivatives, continue to be identified and characterized. In this study, we report the isolation of four new diol esters of OA/DTX-1 from large-scale cultures of Prorocentrum lima. Their chemical structures were elucidated through comprehensive NMR and MS analyses, along with structural comparisons with the well-known OA. Notably, compound 1 featured an additional ester group within the diol unit, while compound 2 was revealed to be a C11 diol ester. The cytotoxicity of these newly isolated derivatives was evaluated against three cell lines: Neuro2a (mouse), HCT116 (human), and HepG2 (human). All diol esters exhibited cytotoxic effects, with compound 3 displaying toxicity comparable to OA. These results expand our understanding of DSP toxin diversity and provide valuable insight into the structural variations and biological activity of diol esters of OA/DTX-1.